0239 Inducible nitric oxide synthase gene methylation and parkinsonism in manganese-exposed welders0239 Inducible nitric oxide synthase gene methylation and parkinsonism in manganese-exposed welders. (23rd June 2014) - Nielsen, Susan; Checkoway, Harvey; Criswell, Susan; Farin, Federico; Racette, Brad
Abstract : Objectives: To assess whether parkinsonism in manganese (Mn)-exposed welders is associated with methylation of NOS2, a methylation-regulated gene that codes for inducible nitric oxide synthase (iNOS). We hypothesised that parkinsonian welders would have lower NOS2 methylation than other welders, consistent with greater iNOS activity and an inflammatory pathogenesis. Method: In a cohort of U. S. shipyard welders we conducted a nested case-control study of parkinsonism and DNA methylation of a NOS2 region previously suggested to be altered with welding exposure. A movement disorders specialist examined each subject using the Unified Parkinson Disease Rating Scale motor subsection 3 (UPDRS3). We included 50 parkinsonian welders as cases (UPDRS3≥15), 105 welders with normal exams (UPDRS3 <6), and 50 welders with an intermediate UPDRS3 score (≥6 to <15), all non-Hispanic Caucasian men 25–65 years of age. We used DNA from whole blood and a pyrosequencing assay for 3 CpG (methylation) sites in NOS2 exon 1. We used unconditional polytomous logistic regression to assess the age-adjusted association between parkinsonism and mean NOS2 methylation. Results: CpG sites were highly methylated (90.8–98.5% mean methylation) among all subjects. Welders with parkinsonism had significantly lower NOS2 methylation than normal welders (odds ratio [OR]=0.69, 95% confidence interval [CI] 0.49–0.97 per 1% absolute increase in methylation). The welders with intermediate UPDRS3 scores also had lower methylation compared to normal welders (OR=0.88, 95% CI 0.65–1.20) (p trend = 0.03). Adjustment for smoking did not alter the results. Conclusions: This study suggests that inflammation mediated by NOS2 gene expression may underlie the pathophysiology of parkinsonism in Mn-exposed welders.